SOCIALIZATION OF THE IMPLEMENTATION OF THE EDUCATION PACKAGE USING POCKET BOOK MEDIA "DAIRY BREAST MILK" - Dewi Andariya Ningsih; Miftakhur Rohmah; Dwi Margareta Andini; Silaturrohmih; Nurhidayati (Community Service Journal of Indonesia, 2023)
Working mothers can breastfeed directly while on maternity leave. After coming to work breastfeeding activities cannot be carried out immediately. However, working mothers continue to breastfeed in a different way while working. To continue to provide breast milk, mothers must express milk. Expressing breast milk can use hands directly with massage techniques and with the help of a breast pump. Working mothers are not free to breastfeed directly like mothers who live at home every day. Working mothers can breastfeed by giving expressed milk. Working mothers have to spend time between working hours to pump breast milk. The result is expressed breast milk that can be packaged and stored in such a way that it can be given to the baby. This activity was comprehensively discussed in the community service activities which were held on March 30, 2021 at the Faculty of Health Sciences Campus. Socialization activities started from registration, pre-test, counseling on breastfeeding, post-test and results recapitulation. Followed by pregnant and lactating women as many as 28 people. In this activity the midwives, pregnant women and breastfeeding mothers were very enthusiastic as evidenced by the many questions that were included in the question-and-answer session because so far many mothers did not understand how to give. This community service is to produce an educational product in the form of a pocket book on how to express breast milk to breastfeeding mothers who work to increase the knowledge of breastfeeding mothers. In this community service, it was found that there was an increase in the knowledge of pregnant and lactating women by using the ASI pocket book media.